Energy solutions for irrigation in Ethiopia - Xie, Hua; Mekonnen, Dawit Kelemework (Applied Research Programme on Energy and Economic Growth, 2022)
The policy brief presents a short summary of a study from the International Food Policy Research Institute (IFPRI) that used an integrated irrigation-energy planning framework to identify groundwater irrigation development potentials in Ethiopia under three energy solutions: grid-connected electricity, off-grid solar PV, and diesel.